Pengaruh Karakteristik Sosial - Ekonomi Masyarakat Terhadap Pola Permukiman di Bantaran / Tepian Sungai Kahayan Kota Palangkaraya - Paddiyatu, Nurhikmah; Pradoto, Wisnu (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Based on RDTR of Palangkarya City in 2009, Kahayan riverside area is included in the green belt /conservation zone. But the facts, there are utilizations of water bodies as residential land, besides; housing problems are growing organically throughout the location of the study area. Based on these points,the purpose of this study is to analyze characteristics of the society based on socio-economic factors that people take into consideration to live there and to know its influence on the pattern of spread of Kahayan riverside settlements in Palangkaraya.Â The approach used in this research is quantitative descriptive and thematic approach. Coverage of discussion / substance in this study is about the socio-economic characteristics of the community as well as the physical characteristics of Kahayan riverside neighborhoods, and the factors that are considered by society to live, as well as its influence on the spread pattern of Kahayan riverside settlement area. As for the results, the overall socio-economic characteristics and environmental influence the characteristics of the settlement pattern in Kahayan riverside area significantly (over 80%). Where the results of the crosstab analysis, variables that have been identified in the economic characteristics such as (livelihood, income level) influence by 82%. While the specific characteristics of social (ethnic) by 76% and physical-environmental characteristics (topography) 88%. It is proved that the socio-economic aspects indirectly affect the patterns of peopleâ€™s settlement. Socio-economic conditions of the riverside area community in the study area indicates that the livelihoods that "near by home" became the reason in preferenced settlement with a dominant percentage, equal to 32.5%. In the aspect of physical condition, the highest percentage of 47.26% with 813 dwellings located on a slope of 0-8% which is lower classification. NNA results obtained dispersed pattern or evenly spread with an index value ratio> 2.58 is equal to 34.3. All the results of analysis are formulated in the zoning plan formulation with resettlement concept and settlement patterns, where the development of settlement patterns are in accordance with socio-economic characteristics in the study area is a grid across the Langkai and Pahandut Seberang villages and pattern combination in the Pahandut village.